Homeownership investment and tax neutrality: A joint assessment of income and property taxes in Europe - Francesco Figari; Gerlinde Verbist; Francesca Zantomio (University of Essex, Institute for Social and Economic Research (ISER), 2019)
Western countries' income tax systems exempt the return from investing in owner-occupied housing. Returns from other investments are instead taxed, thus distorting households' portfolio choices, although it is argued that housing property taxation might act as a counterbalance. Based on data drawn from the Statistics of Income and Living Conditions and the UK Family Resources Survey, and building on tax-benefit model EUROMOD, we provide novel evidence on the interplay of income and property taxation in budgetary, efficiency and equity terms in eight European countries. Results reveal that, even accounting for recurrent housing property taxation, a sizeable 'homeownership bias' i.e. a lighter average and marginal taxation for homeownership investment, is embedded in current tax systems, and displays heterogeneous distributional profiles across different countries. Housing property taxation represents only a partial correction towards neutrality.
Keywords: D31; H23; I31; I32; 330; Homeownership investment; tax neutrality; income tax; property tax; distributional effect; Europe; microsimulation